Pengaruh Fungsi Badan Pengawas, Sistem Pengendalian Internal, Dan Kompetensi Sumber Daya Manusia Terhadap Kinerja Lembaga Perkreditan Desa ( LPD) Se-Kecamatan Tampaksiring - Ni Putu Novika Yuni; Kadek Dewi Padnyawati; Ni Wayan Alit Erlina Wati (UNHI Press, 2025)
The LPD has such an important role for the village community that it must produce the best performance every time. Company performance is the result or work performance of good managerial management which is expected to be able to improve a company's goals. This study aims to determine the influence of the Functions of the Oversight Body, Internal Control System and Competence of Human Resources on the Financial Performance of Village Credit Institutions (LPD) throughout the Tampaksiring District. The population in this study were 136 respondents from the LPD management who assessed and knew directly the performance of the LPD, consisting of the LPD Chair, Secretary, Treasurer, and Chair of the Supervisory Board from 34 LPDs in the Tampaksiring District.. This study uses the probability sampling method saturated sample technique. Saturated sample is a sampling technique when all members of the population are used as samples. The test results show that the function of the oversight body has a significant positive effect on the performance of the LPD in the Tampaksiring District. The internal control system has a significant positive effect on the performance of the LPD in the Tampaksiring District. HR competence has a significant positive effect on the performance of LPD in Tampaksiring District. For further research, it is expected to be able to add variables that can affect LPD performance and be able to expand the research area.